Preparation method of transition metal oxide nanowire / MXene composite modified diaphragm and application of the modified diaphragm
By using transition metal oxide nanowires and MXene composite materials in the lithium-sulfur battery separator for modification, the problems of short life and low circulation performance of lithium-sulfur battery are solved, longer life and better conductivity are achieved, and the process is simple. , low cost.
Patent Information
- Application Number
- CN202211367359.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-11-03
AI Technical Summary
The lithium-sulfur battery has a short life and low cycling performance, which is mainly due to the shuttle effect of polysulfur ions, which reduce the battery capacity. The existing technology modification methods have problems such as high raw material costs, heavy metal ions, and cumbersome preparation processes.
Transition metal oxide nanowires and MXene composites are used to modify the separator, and combined with commercially available polyolefin separator through layer-to-layer self-assembly technology to form a modified separator with good ion selectivity and conductivity.
It significantly extends the life of lithium-sulfur batteries, improves its circulation performance and conductivity, and is simple in preparation and low in cost, which has industrial application value.
Smart Images

Figure CN115764155B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a transition metal oxide nanowire / MXene composite modified diaphragm and application of the modified diaphragm as a lithium-sulfur battery diaphragm, in particular to modification technology and application of polyolefin diaphragms such as polyethylene and polypropylene, belonging to the technical field of lithium-ion batteries and lithium-sulfur batteries. Background Art
[0002] At present, the diaphragm materials widely commercialized in the field of lithium-ion batteries are mainly polyethylene and polypropylene microporous membranes. Lithium-sulfur battery is a type of lithium-ion battery and a high-performance energy storage battery. Its advantages and disadvantages are very obvious. The advantage is that the raw material elemental sulfur is cheap and easy to obtain, and the capacity of the molded battery is about ten times that of the lithium battery on the market, which has great application prospects; the disadvantage is that the introduction of elemental sulfur reduces the conductivity and cycle performance of the battery. The goal of improvement is to ensure the retention rate of lithium-sulfur batteries with large capacity and long cycles. With the development of large-capacity energy storage equipment and power lithium-ion batteries, the market has put forward higher and more stringent requirements for high-performance diaphragm materials. At present, the diaphragm materials widely commercialized in the field of lithium-ion batteries are mainly polyethylene and polypropylene microporous membranes. Due to the low lithium storage potential, there is an uneven deposition of lithium, which has huge safety hazards, and there are disadvantages such as low lithium storage capacity and poor cycle performance. At present, the capacity of lithium-sulfur batteries on the market is 800 mAh / g in the first cycle, and only 400 mAh / g of specific capacity is retained after 100 cycles, and the life is relatively low. With the development of large-capacity energy storage devices and power lithium / sodium-ion batteries, the market has put forward higher and more stringent requirements for high-performance diaphragm materials.
[0003] For existing technologies, the urgent problem that lithium-sulfur batteries need to solve is their short life and low cycle performance. The problem is that polysulfide ions shuttle through the diaphragm and accumulate at the negative electrode, resulting in a decrease in battery capacity. Current technology shows that modifying the diaphragm can effectively reduce this problem. Although the existing technology can improve the life and capacity of lithium-sulfur batteries to a certain extent, it often has disadvantages such as high raw material costs, heavy metal ions, and complicated preparation processes. For example, the MnFe2O4-modified diaphragm material studied by Yang Wang's team from the School of Chemical Engineering of Sichuan University (Wang Y, Guo X, Chen C, et al. Alleviating the shuttle effect via bifunctional MnFe2O4 / AB modified separator for high performance lithium sulfur battery[J]. Electrochimica Acta, 2020, 354.) requires an activation operation when preparing the diaphragm, which requires the use of organic solvent NMP and a binder, and the preparation process is relatively cumbersome. In the master's thesis "Preparation and Electrochemical Performance Study of MXene-based Lithium-Sulfur Battery Diaphragm Modified Materials" by Li Juan of Harbin Normal University, Ti3C2T x -PEDOT:PSS material modified lithium-sulfur battery separator, while still using organic solvents, its initial usage is still low.
[0004] Considering the linear structure of transition metal oxide nanowires, they have good blocking properties for polysulfide ions and can ensure the cycle performance. At the same time, MXene has good conductivity and planar structure, which is conducive to the penetration of lithium ions.
[0005] In view of this, the inventors of the present invention tried for the first time to add a mixed material of transition metal oxide nanowires and MXene to the traditional commercial PP separator to improve the performance of lithium-sulfur batteries and extend their life. Summary of the invention
[0006] In view of the serious shuttle effect and short life of the current lithium-sulfur batteries, the present invention first provides a method for preparing a transition metal oxide nanowire / MXene composite modified diaphragm, and composites MXene on the basis of the previous transition metal oxide nanowire, using its structure to effectively block macromolecular polysulfide ions, and MXene has ion channels, which is conducive to enhancing conductivity. In addition, the present invention also provides the application of the transition metal oxide nanowire / MXene composite modified diaphragm as a lithium-sulfur battery diaphragm.
[0007] In the first aspect of the present invention, a method for preparing a transition metal oxide nanowire / MXene composite modified membrane is provided, the steps of which are as follows: adding transition metal oxide nanowires and MXene in a mass ratio of 2 to 98: 2 to water, and preparing a diaphragm having a concentration of 0.33-1.67 mg·ml by high-speed stirring and ultrasonic dispersion technology. -1 The present invention adopts layer-by-layer self-assembly technology, uses commercially available polyolefin membranes as filter paper and substrate, and obtains the modified membrane by suction filtration.
[0008] Furthermore, the transition metal oxide nanowires are linear structures with a diameter less than 100 nanometers and a length between 1 and 500 micrometers.
[0009] Furthermore, the transition metal oxide nanowires are titanium oxide nanowires, and tetrabutyl titanate is used as the optimal titanium source.
[0010] Furthermore, the transition metal in the transition metal oxide nanowires is other transition metal oxide nanowires except titanium metal, and sulfate is the best metal source.
[0011] Furthermore, the preparation method of the transition metal oxide nanowires is as follows: the transition metal oxides are prepared by solvothermal reaction. According to actual needs, some oxides (such as titanium dioxide nanowires) need to be obtained by calcining the nano-solvothermal product under the protection of inert gas.
[0012] Preferably, the reaction temperature of the solvent thermal reaction is 160-220° C., and the reaction time is 12-24 hours.
[0013] Preferably, the calcination temperature is 500-750 degrees Celsius, the calcination time is 8-14 hours, and the inert gas is preferably argon.
[0014] In a preferred embodiment of the present invention, the transition metal oxide nanowires are titanium dioxide nanowires, and the preparation steps are as follows: tetrabutyl titanate is used as a titanium source, sodium hydroxide is used as an oxygen source, ethanol is used as a solvent to dissolve tetrabutyl titanate, and water is used as a solvent to dissolve sodium hydroxide, and then the mixture is uniformly mixed and then subjected to a solvothermal reaction. A more preferred ratio is: a molar ratio of tetrabutyl titanate to sodium hydroxide of 0.02. After the reaction is completed, the precipitate is extracted, washed, and dried to obtain titanium dioxide nanowires. In this step, if the temperature is too low and the reaction time is too short, titanium dioxide nanosheets will be formed, which will affect the performance of the product.
[0015] In a preferred embodiment of the present invention, the transition metal oxide nanowires are other transition metal oxide nanowires, such as vanadium pentoxide nanowires, chromium trioxide nanowires, manganese dioxide nanowires, iron trioxide nanowires, cobalt oxide nanowires, nickel oxide nanowires, copper oxide nanowires, silicon dioxide nanowires or aluminum oxide nanowires, and the preparation steps are as follows: sulfate is used as a metal ion source, some metal ions require sodium hydroxide as an oxygen source and a precipitant, and some ions require ammonium persulfate as an oxidant, water is used as a solvent to dissolve sulfate, water is used as a solvent to dissolve sodium hydroxide and ammonium persulfate, and then a solvent thermal reaction is carried out after mixing evenly. The optimal molar ratio of sulfate to sodium hydroxide is 0.033. After the reaction is completed, the precipitate is washed, dried and ground to obtain nanowires. In this step, if the ratio deviates, there will be microscopic defects in the generated oxide nanowires, affecting the performance.
[0016] Furthermore, the preparation method of MXene is as follows: using MAX (Ti-Al-C) as a raw material, adding hydrochloric acid and lithium fluoride as an etchant, preparing a MXene precursor through a water bath reaction, separating the MXene precipitate by centrifugation, allowing it to continue to react by ultrasonication under an argon atmosphere, and finally centrifuging to obtain a MXene dispersion.
[0017] Preferably, the water bath temperature is 40-70° C., and the reaction time is 20-26 hours.
[0018] Preferably, the centrifugal speed is 3000-3800 rpm, the time is 3 minutes once, a total of six times, and the precipitate is taken. In this operation, if the number of washing times is too small, Al ions will remain in the product, affecting the structural plane and purity of the product, and ultimately causing the battery performance to decline.
[0019] Preferably, the ultrasonic treatment is performed under argon atmosphere for 1-4 hours.
[0020] Preferably, the ultrasonic treatment is followed by centrifugation again at a rate of 3000-3800 rpm for 20-50 minutes. This step is to fully separate the product from the impurities. Insufficient centrifugation will also result in reduced product quality.
[0021] In a second aspect of the present invention, there is provided an application of a transition metal oxide nanowire / MXene composite modified diaphragm prepared by the method of the first aspect as a diaphragm material for a lithium-sulfur battery.
[0022] The principle of the present invention is as follows: the present invention can obtain a nanowire-shaped titanium dioxide structure by a solvothermal reaction between tetrabutyl titanate and sodium hydroxide, and then obtain titanium dioxide nanowires by annealing. Other transition metal oxide nanowires having a linear structure can also be prepared by a solvothermal reaction using transition metal sulfates and sodium hydroxide. MXene material is obtained by HF etching the Al element on the Max material, and then the MXene material and the transition metal oxide nanowires are ultrasonically mixed to obtain a transition metal oxide nanowire / MXene composite material, and then a transition metal oxide nanowire / MXene composite material modified diaphragm is prepared.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] 1) Compared with traditional diaphragms and titanium dioxide nanowire modified diaphragms, the transition metal oxide nanowire / MXene composite modified diaphragm of the present invention has better ion selective permeability, which is macroscopically manifested as a longer life and better conductivity.
[0025] 2) The method of the present invention can produce special tubular structure titanium dioxide nanowires by first preparing a nanoscale tubular precursor and then annealing it to form a composite material; moreover, the method of the present invention is simple in preparation, short in cycle, and uses cheap and readily available raw materials, which is low in cost and has great industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM of titanium dioxide nanowires.
[0027] Figure 2 XRD of the TiO2 nanowire / MXene material modified diaphragm.
[0028] Figure 3 The long cycle performance of a lithium-sulfur battery equipped with a titanium dioxide nanowire / MXene material modified diaphragm according to Example 1 of the present invention and a common lithium-sulfur battery with a diaphragm on the market is compared.
[0029] Figure 4 The long cycle performance of the lithium-sulfur battery equipped with the manganese dioxide nanowire / MXene material modified membrane of Example 4 of the present invention.
[0030] Figure 5 The long cycle performance of the lithium-sulfur battery equipped with the vanadium pentoxide nanowire / MXene material modified membrane of Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0032] The Mxene used in the present invention is purchased from Jilin Yiyi Co., Ltd., tetrabutyl titanate and other transition metal sulfates are purchased from Aladdin, and the polypropylene microporous diaphragm is purchased from Aladdin.
[0033] Example 1
[0034] The preparation method of titanium dioxide nanowires is as follows:
[0035] Take 12g of sodium hydroxide and dissolve it in 30ml of water, stir it thoroughly and dissolve it. Take 2.08ml of tetrabutyl titanate and dissolve it in 30ml of ethanol, stir it thoroughly and dissolve it. Mix the two under stirring and stir for another 30 minutes. Put it into the reactor and react it at 190 degrees Celsius for 18 hours. After the reaction is completed, wash it with dilute hydrochloric acid and pure water three times respectively, then dry it for 12 hours, and calcine it at 550℃ for 10 hours.
[0036] The preparation method of MXene is as follows:
[0037] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0038] The preparation method of the modified diaphragm is as follows:
[0039] 150 mg of the prepared titanium dioxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0040] Titanium dioxide nanowires and MXene were added to water in a mass ratio of 1:1, and the concentration was between 0.33 mg ml by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and matrix to obtain the titanium dioxide nanowire / MXene material modified membrane.
[0041] Figure 1 This is a SEM image of titanium dioxide nanowires. It can be observed that they are linear and about 1um long.
[0042] Figure 2XRD of titanium dioxide nanowire / MXene material modified diaphragm. Figure 2 It can be seen that the material has obvious absorption peaks of B-type titanium dioxide and obvious peaks of C / Ti compounds.
[0043] Example 2
[0044] The preparation method of vanadium pentoxide nanowires is as follows:
[0045] Take 4.564g of ammonium persulfate, 7.68g of vanadium (III) sulfate, and 13.213g of ammonium sulfate and dissolve them in 50ml of pure water respectively. After stirring evenly, pour the vanadium sulfate solution and the ammonium persulfate solution into the ammonium sulfate solution under stirring, stir for two hours, and then put it into a forced air drying oven for solvent thermal reaction at 200°C for 48 hours. After the reaction, wash, filter, dry, and grind to obtain the product.
[0046] The preparation method of MXene is as follows:
[0047] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0048] The preparation method of the modified diaphragm is as follows:
[0049] 150 mg of the prepared vanadium pentoxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0050] Vanadium pentoxide nanowires and MXene were added to water at a mass ratio of 2:1, and a concentration of 0.45 mg ml was obtained by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and the matrix to obtain the vanadium pentoxide nanowire / MXene material modified membrane.
[0051] Example 3
[0052] Preparation method of chromium trioxide nanowires:
[0053] Take 5g of chromium sulfate hexahydrate and 12g of sodium hydroxide and dissolve them in 60ml of pure water respectively. After stirring evenly, pour the chromium sulfate solution into the ammonium sulfate solution while stirring. After stirring for three hours, put it into a blast drying oven and perform solvent thermal reaction at 180℃ for 36 hours. After the reaction, wash it with clean water three times in turn, dry it, and grind it to obtain the product.
[0054] Preparation of MXene: The method is the same as Example 1.
[0055] The preparation method of the modified diaphragm is as follows:
[0056] 150 mg of the prepared chromium oxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0057] Chromium oxide nanowires and MXene were added to water at a mass ratio of 5:1, and a concentration of 0.65 mg ml was obtained by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and the matrix to obtain the chromium trioxide nanowire / MXene material modified membrane.
[0058] Example 4
[0059] Preparation method of manganese dioxide nanowires:
[0060] Take 4.564g of ammonium persulfate, 3.3804g of manganese sulfate monohydrate, and 13.213g of ammonium sulfate and dissolve them in 50ml of pure water respectively. After stirring evenly, pour the manganese sulfate solution and the ammonium persulfate solution into the ammonium sulfate solution under stirring, stir for two hours, and then put it into a forced air drying oven for solvent thermal reaction at 200℃ for 48 hours. After the reaction, wash, filter, dry and grind to obtain the product.
[0061] The preparation method of MXene is as follows:
[0062] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0063] The preparation method of the modified diaphragm is as follows:
[0064] 150 mg of the prepared manganese dioxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0065] Manganese dioxide nanowires and MXene were added to water in a mass ratio of 8:1, and a uniform mixed dispersion with a concentration of 0.45 mg·ml-1 was obtained by high-speed stirring and ultrasonic dispersion technology. Then, fluid-guided self-assembly technology was used to obtain a manganese dioxide nanowire / MXene material modified membrane with commercially available polypropylene microporous membrane as the filter membrane and matrix.
[0066] Example 5
[0067] The preparation method of ferric oxide nanowires is as follows:
[0068] Take 5.08g of ferrous sulfate hexahydrate and 12g of sodium hydroxide and dissolve them in 50ml of pure water respectively. After stirring evenly, pour the chromium sulfate solution into the sodium hydroxide solution under stirring. After stirring for three hours, put it into a blast drying oven and perform solvent thermal reaction at 195℃ for 36 hours. After the reaction, wash it with clean water three times in turn, then dry it for 12 hours, and calcine it at 500℃ for 8 hours to obtain the product.
[0069] The preparation method of MXene is as follows:
[0070] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing agent is dilute hydrochloric acid, and the last three times of washing agent is pure water. Adjust pH=7 and ultrasonicate it in argon atmosphere. After the ultrasonicate is finished, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene. Take 150mg of the prepared vanadium pentoxide nanowires and dissolve them in 450ml of anhydrous ethanol, add 450mg PVP as a binder, and seal it for later use.
[0071] The preparation method of the modified diaphragm is as follows:
[0072] 150 mg of the prepared ferric oxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0073] Iron oxide nanowires and MXene were added to water at a mass ratio of 25:1, and the concentration was between 0.95 mg ml by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and the matrix to obtain the iron oxide nanowire / MXene material modified membrane.
[0074] Example 6
[0075] The preparation method of cobalt oxide nanowires is as follows:
[0076] Take 3.11g of anhydrous cobalt sulfate and 8g of sodium hydroxide and dissolve them in 50ml of pure water respectively. After stirring evenly, pour the cobalt sulfate solution into the sodium hydroxide solution under stirring. After stirring for three hours, put it into a blast drying oven at 195℃ for solvent thermal reaction for 36 hours. After the reaction, wash it with clean water for 3 times. Dry it and grind it to obtain the product.
[0077] The preparation method of MXene is as follows:
[0078] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0079] The preparation method of the modified diaphragm is as follows:
[0080] 150 mg of the prepared vanadium pentoxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0081] Cobalt oxide nanowires and MXene were added to water at a mass ratio of 35:1, and the concentration was between 1 mg ml by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and matrix to obtain the cobalt oxide nanowire / MXene material modified membrane.
[0082] Example 7
[0083] The method for preparing nickel oxide nanowires is as follows:
[0084] Take 5.26g nickel sulfate hexahydrate and 8g sodium hydroxide and dissolve them in 70ml pure water respectively. After stirring evenly, pour the nickel sulfate solution into the sodium hydroxide solution under stirring. After stirring for three hours, put it in a blast drying oven at 195℃ for solvent thermal reaction for 36 hours. After the reaction, wash it with clean water three times in turn. Dry it and grind it to obtain the product.
[0085] The preparation method of MXene is as follows:
[0086] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0087] The preparation method of the modified diaphragm is as follows:
[0088] 150 mg of the prepared nickel oxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0089] Nickel oxide nanowires and MXene were added to water at a mass ratio of 75:2, and a concentration of 1.25 mg ml was obtained by high-speed stirring and ultrasonic dispersion. -1The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and matrix to obtain the nickel oxide nanowire / MXene material modified membrane.
[0090] Example 8
[0091] The method for preparing copper oxide nanowires is as follows:
[0092] Take 5g of copper sulfate pentahydrate and 6g of sodium hydroxide and dissolve them in 70ml of pure water respectively. After stirring evenly, pour the copper sulfate solution into the sodium hydroxide solution while stirring. After stirring for three hours, put it into a blast drying oven and react with solvent heat at 170℃ for 24 hours. After the reaction, wash it with clean water three times in turn, dry it, and grind it to obtain the product.
[0093] The preparation method of MXene is as follows:
[0094] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH to 7, then ultrasonicate it in argon atmosphere, and centrifuge it at 3500 rpm for 30 minutes after the ultrasonication to obtain Mxene.
[0095] The preparation method of the modified diaphragm is as follows:
[0096] 150 mg of the prepared copper oxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0097] Copper oxide nanowires and MXene were added to water at a mass ratio of 40:1, and the concentration was between 1.45 mg ml by high-speed stirring and ultrasonic dispersion. -1 The copper oxide nanowire / MXene material modified membrane was obtained by using the fluid-guided self-assembly technology and commercially available polypropylene microporous membrane as the filter membrane and matrix.
[0098] Example 9
[0099] The method for preparing silica nanowires is as follows:
[0100] Take 4.8g of sodium silicate and dissolve it in 50ml of pure water. After stirring evenly, add 15ml of 1M dilute hydrochloric acid while stirring. After stirring for three hours, wash and dry to obtain the product.
[0101] The preparation method of MXene is as follows:
[0102] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0103] The preparation method of the modified diaphragm is as follows:
[0104] 150 mg of the prepared silica nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0105] Silica nanowires and MXene were added to water at a mass ratio of 85:2, and the concentration was between 1.5 mg ml by high-speed stirring and ultrasonic dispersion. -1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to obtain a silica nanowire / MXene material modified membrane with a commercially available polypropylene microporous membrane as the filter membrane and matrix.
[0106] Example 10
[0107] The preparation method of aluminum oxide nanowires is as follows:
[0108] Take 8.55g of aluminum sulfate and 6g of sodium hydroxide and dissolve them in 40ml of pure water respectively. After stirring evenly, pour the copper sulfate solution into the sodium hydroxide solution while stirring. After stirring for three hours, put it into a blast drying oven and react with solvent heat at 190℃ for 24 hours. After the reaction, wash it with clean water three times in turn, dry it, and grind it to obtain the product.
[0109] The preparation method of MXene is as follows:
[0110] Take 1g Max and etch it with 10.8mL HCl and 1.6g LiF at 60℃ for 24 hours, then centrifuge it at 3500 rpm for 6 times. The first three times of washing are with dilute hydrochloric acid, and the last three times of washing are with pure water. Adjust pH=7, then ultrasonicate it in argon atmosphere, and after the end of ultrasonicate, centrifuge it again at 3500 rpm for 30 minutes to obtain Mxene.
[0111] The preparation method of the modified diaphragm is as follows:
[0112] 150 mg of the prepared aluminum oxide nanowires were dissolved in 450 ml of anhydrous ethanol, 450 mg of PVP was added as a binder, and the mixture was sealed for later use.
[0113] Alumina nanowires and MXene were added to water at a mass ratio of 98:2, and a concentration of 1.67 mg ml was obtained by high-speed stirring and ultrasonic dispersion.-1 The uniformly mixed dispersion was prepared, and then the fluid-guided self-assembly technology was used to take the commercially available polypropylene microporous membrane as the filter membrane and the matrix to obtain the alumina nanowire / MXene material modified membrane.
[0114] Embodiment 11
[0115] The titanium dioxide nanowire / MXene composite material prepared in Example 1 is used as a lithium-sulfur battery diaphragm material. The lithium-sulfur battery assembly process is as follows: sulfur powder, carbon black, and PVDF (polyvinylidene fluoride) are stirred in 1.25ml NMP (N-methylpyrrolidone) according to a mass ratio of 0.8g, 0.16g, and 0.04g for 12 hours, and the mixture is evenly coated on aluminum foil by a spatula using a cast method, and vacuum dried for 12 hours as the battery positive electrode. Operate in an argon atmosphere glove box to assemble button cells, the positive electrode is the prepared positive electrode, the negative electrode is a purchased metal sodium sheet, the diaphragm is the titanium dioxide nanowire / MXene composite material prepared in Example 1, and the electrolyte is an LSB-P type electrolyte.
[0116] According to the above-mentioned lithium-sulfur battery assembly method, the only difference is that the diaphragm is replaced with a commercially available polyolefin diaphragm, and an ordinary lithium-sulfur battery of the prior art is prepared for comparison.
[0117] Using the Blue Power Battery Test System, connect the assembled battery to the test terminal and set the battery performance to be tested at 0.1C, 0.2C, and 0.5C rates. The test results are exported to Excel and plotted using drawing software.
[0118] The long cycle performance comparison results of the lithium-sulfur battery equipped with the titanium dioxide nanowire / MXene material modified diaphragm of Example 1 of the present invention and the ordinary lithium-sulfur battery with diaphragm on the market are as follows: Figure 3 As shown. Figure 3 It can be seen that after the cycle test, the present invention can still maintain a relatively high capacity. If the capacity is less than 600 mA·h as scrapped, the life of the present invention is much longer than that of traditional lithium-sulfur batteries.
[0119] in addition,
[0120] The manganese dioxide nanowire / MXene material prepared in Example 4 was used as the separator material for the lithium-sulfur battery. The lithium-sulfur battery was assembled according to the above-mentioned lithium-sulfur battery assembly method. The long cycle performance of the lithium-sulfur battery was tested using the same test system as above. The results are as follows: Figure 4 shown.
[0121] The vanadium pentoxide nanowire / MXene material prepared in Example 2 was used as a lithium-sulfur battery separator material, and a lithium-sulfur battery was assembled according to the above-mentioned lithium-sulfur battery assembly method. The long cycle performance of the lithium-sulfur battery was tested using the same test system as above. Figure 5 shown.
[0122] from Figure 4 and Figure 5 It can be seen that the performance of batteries equipped with manganese dioxide nanowire / MXene or vanadium pentoxide nanowire / MXene membranes is similar to that of batteries equipped with titanium dioxide nanowire / MXene membranes, and the capacity is significantly improved compared to ordinary lithium-sulfur batteries.
[0123] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a transition metal oxide nanowire / MXene composite modified diaphragm, characterized in that: The steps are as follows: Add transition metal oxide nanowires and MXene in a mass ratio of 2 to 98:2 into water, and use high-speed stirring and ultrasonic dispersion technology to obtain a concentration between 0.33 and 1.67 mg ml -1 A uniformly mixed dispersion is prepared, and then a fluid-guided self-assembly technique is used, and a polyethylene or polypropylene microporous membrane is used as a filter membrane and a matrix to obtain a transition metal oxide nanowire / MXene composite modified membrane; The preparation method of MXene is as follows: MAX is used as a raw material, hydrochloric acid and lithium fluoride are added as an etchant, a MXene precursor is prepared by a water bath reaction, the MXene precipitate is separated by centrifugation, the MXene is allowed to continue to react by ultrasonication under an argon atmosphere, and finally centrifuged to obtain a MXene dispersion; In the water bath reaction, the water bath temperature is 40-70°C and the reaction time is 20-26 hours; In the centrifugal separation of MXene precipitates, the centrifugal speed is 3000-3800 rpm, the time is 3 minutes once, a total of six times, and the precipitate is taken each time; Ultrasonication under the argon atmosphere for 1-4 hours; After ultrasonic treatment, the mixture was centrifuged again at a speed of 3000-3800 rpm for 20-50 min.
2. The preparation method according to claim 1, characterized in that: The transition metal oxide nanowires are titanium oxide nanowires, and tetrabutyl titanate is used as a titanium source.
3. The preparation method according to claim 1, characterized in that: The transition metal in the transition metal oxide nanowires is a transition metal oxide nanowire other than metal titanium, and sulfate is the best metal source.
4. The preparation method according to claim 1, characterized in that: The preparation method of the transition metal oxide nanowires is as follows: preparing the transition metal oxide by solvent thermal reaction; the reaction temperature of the solvent thermal reaction is 160-220° C., and the reaction time is 12-24 hours.
5. The preparation method according to claim 4, characterized in that: When the transition metal oxide nanowires are titanium oxide nanowires, the nanosolvothermal product is calcined under the protection of an inert gas, the calcination temperature is 500-750 degrees Celsius, the calcination time is 8-14 hours, and the inert gas is argon.
6. The preparation method according to claim 1, characterized in that: The transition metal oxide nanowires are titanium dioxide nanowires, and the preparation steps are as follows: tetrabutyl titanate is used as a titanium source, sodium hydroxide is used as an oxygen source, ethanol is used as a solvent to dissolve tetrabutyl titanate, water is used as a solvent to dissolve sodium hydroxide, and the mixture is evenly mixed and then subjected to a solvothermal reaction.
7. The preparation method according to claim 1, characterized in that: The transition metal oxide nanowires are vanadium pentoxide nanowires, chromium trioxide nanowires, manganese dioxide nanowires, iron trioxide nanowires, cobalt oxide nanowires, nickel oxide nanowires, copper oxide nanowires, silicon dioxide nanowires or aluminum oxide nanowires, and the preparation steps are as follows: sulfate is used as a metal ion source, sodium hydroxide is used as an oxygen source and a precipitant, or ammonium persulfate is used as an oxidant, water is used as a solvent to dissolve sulfate, water is used as a solvent to dissolve sodium hydroxide and ammonium persulfate, and the mixture is evenly mixed and then subjected to a solvothermal reaction.
8. Use of a transition metal oxide nanowire / MXene composite modified diaphragm prepared by the preparation method according to any one of claims 1 to 7 as a diaphragm material for a lithium-sulfur battery.
Citation Information
Patent Citations
Lithium manganese phosphate and carbon nano tube / fiber composite material and preparation method thereof as well as positive electrode of lithium ion secondary battery and battery
CN104241643A
MXene modified composite diaphragm, preparation method thereof, and application in lithium-sulphur battery
CN107369801A